(untitled) (TEST Ticontre. Theory Text Translation, 2022)
Die Elenden (The Wretched) by Anna Mayr is both an autobiographical reportage and a documentary essay on the theme of structural unemployment in reunified Germany. The author starts from her own experience as the daughter of unemployed people, supported by the state subsidy Hartz IV. She then describes the social marginalization associated with unemployment both from the inside and from the perspective of those who, by working, lead a socially accepted existence. In the context of advanced capitalism, the author reflects on the role of work, alienating in the known sense and at the same time depriving of any authentic meaning not only for those who work but also for those who do not have a job. The memoir deals with the contradiction between the necessity of unemployment, implicit in capitalism, and its removal as a spectre of possible social decline.Finally, the author criticizes the reformist mechanisms that are immanent in the system that produces unemployment, but ultimately aim at consolidating the status quo, without questioning it.